Effect of a STEM approach on students' cognitive structures about electrical circuits - Mónica Baptista; Iva Martins (SpringerOpen, 2023)
Abstract Background Electricity is a central concept in science curricula at all levels of education. Nevertheless, its invisible nature makes the concepts associated with it very difficult for students. Moreover, students have many alternative conceptions about concepts related to electrical circuits. This study aims to know the effect of a STEM (Science-Technology-Engineering-Mathematics) approach on students' cognitive structures about the topic of electrical circuits, as revealed through a Word Association Test (WAT). A study following a time series quasi-experimental research design was made to collect information about changes in students' cognitive structures before and after a learning sequence about electrical circuits. A nonequivalent control group approach was used, and two matching groups of students were used: a control group (N = 317) and an experimental group (N = 321). Students were attending the 9th grade (14-15 years old). Data analysis was made by construction of frequency tables, maps of the cognitive structures, and examination of the sentences written by students. Results The results are indicative that, before the STEM approach, students' conceptions regarding electrical circuits are mainly related to students' daily experiences. However, after a STEM approach, the map of students' cognitive structures from the experimental group is more complex. Furthermore, the quality of the response words is different for each group. In the control group, most of the associations that students made were situated at a phenomenological level. However, in the experimental group, students made many associations related to the curricular contents. Conclusions The STEM approach had a more noticeable effect on the development of students' cognitive structures on the topic of electrical circuits: based on the results, it can be concluded that this approach allowed students from the experimental group to achieve the learning goals, while students from the control group still retained many ideas that do not meet learning goals. Additionally, WAT has proven to be a suitable diagnostic method, as well as an instrument that can be used to evaluate the accomplishment of students' learning objectives.